Inhibition of phospho-MurNAc-pentapeptide translocase (MraY) by nucleoside natural product antibiotics, bacteriophage ϕX174 lysis protein E, and cationic antibacterial peptides. Issue 24 (15th December 2016) - Bugg, Timothy D.H.; Rodolis, Maria T.; Mihalyi, Agnes; Jamshidi, Shirin
Graphical abstract: Abstract: This review covers recent developments in the inhibition of translocase MraY and related phospho-GlcNAc transferases WecA and TagO, and insight into the inhibition and catalytic mechanism of this class of integral membrane proteins from the structure of Aquifex aeolicus MraY. Recent studies have also identified a protein–protein interaction site in Escherichia coli MraY, that is targeted by bacteriophage ϕX174 lysis protein E, and also by cationic antimicrobial peptides containing Arg-Trp close to their N- or C-termini.